Weighting the factors affectıng logıstıcs outsourcıng - Karamaşa, Çağlar; Demir, Ezgi; Memiş, Salih; Korucuk, Selçuk (Decision Making: Applications in Management and Engineering, 2021)
Today, growing and changing competitive conditions, products and services, free movement of labor and businesses with the information they develop strategies that create value in order to obtain a competitive advantage. Now, final buyers have the convenience of purchasing the products they demand with the features and conditions they want and at the price they accept. In such an environment, businesses use their supply chain and logistics activities more effectively and efficiently than their competitors. Today, achieving a strategic superiority in a global market where the content and quality of the products are the same is only possible by delivering the desired products to the customer at the desired price, at the desired time, in the desired amount, through the right channel, as quickly as possible and without any damage. In such a situation, the desire to focus on the main activities of the enterprises, the need for effective logistics operations, etc. logistics outsourcing has increasing rapidly for reasons. Businesses can carry out logistics activities requiring expertise thanks to third party logistics (3PL) service providers in the field such as transportation, storage, customs clearance, without investing in logistics. In order for logistics outsourcing to be beneficial, a correct logistics service provider must be selected in accordance with the needs of the business. Selecting the right logistics service provider is important in increasing the benefit of outsourcing. In this study neutrosophic AHP was used to prioritize the factors.